Intravenous lacosamide for treatment of absence status epilepticus in genetic generalized epilepsy: A case report and review of literature. (6th April 2018) - Reif, P. S.; Männer, A.; Willems, L. M.; Kay, L.; Zöllner, J. P.; Klein, K. M.; Rosenow, F.; Strzelczyk, A.
Abstract : Background: Nearly 10 years after its introduction into the market, the significance of lacosamide in genetic generalized epilepsies is still unclear. Its new mode of action may qualify lacosamide as a therapeutic agent in this entity, but only a limited number of cases have been published so far. Aim: To describe the efficacy of lacosamide as treatment in a patient with the absence status epilepticus. Method: We report on a 28‐year‐old woman with genetic generalized epilepsy who suffered recurrent absence status epilepticus during video‐EEG‐monitoring. After treatment failure of first‐ and second‐line medication, lacosamide was administered. The outcome in this patient was evaluated, and a systematic literature review was performed for the use of lacosamide in the absence status epilepticus. Results: After application of 400 mg lacosamide intravenously, the absence status epilepticus terminated within 30 minutes. No further seizures or epileptiform discharges reoccurred until the end of video‐EEG‐Monitoring 3 days later. Conclusions: The role of lacosamide as a therapeutic option in patients with the absence status epilepticus is unclear. Only two cases have been reported so far with conflicting results. Further randomized controlled studies are required to validate the relevance of lacosamide as treatment for status epilepticus in genetic generalized and the absence epilepsy.